Tinjauan Hukum Adat terhadap Kedudukan Anak Luar Kawin (An Nasi) dalam Pembagian Warisan Berdasarkan Hukum Adat Suku Timor di Kecamatan Amarasi Barat - Yana Elda Kaseh; Juliana Susantje Ndolu; Chatryen M. Dju Bire (Student Scientific Creativity Journal, 2026)
This study aims to determine the status of illegitimate children (An Nasi) according to the customary inheritance law of the Timorese people in West Amarasi District, especially Teunbaun Village, as well as the form of inheritance obtained. This study is motivated by customary law practices that provide space for illegitimate children to obtain recognition and certain rights from the father, although the implementation has not been fully fulfilled. The method used is empirical legal research with a sociological juridical approach through interviews and literature studies. The results of the study indicate that illegitimate children are more accepted in the mother’s family, while recognition from the father is still limited and must also undergo a customary process, namely Mbaena Hae. In practice, the position of illegitimate children is highly dependent on customary deliberations and social acceptance within the community. Although customary law provides certain mechanisms for recognition, their implementation is not uniform across all families and is influenced by social norms, kinship structures, and community agreements. Furthermore, inheritance rights obtained by illegitimate children tend to be limited and symbolic rather than equal to legitimate children. These findings highlight the persistence of customary values in regulating family relations and inheritance distribution in Timorese society.